The operator's response to P2P service demand. - Liotta, Antonio (IEEE Communications magazine)
Peer-to-peer (P2P) systems are in high demand for all sorts of tasks-video communication, resource sharing, and content retrieval, to mention a few. However, current P2P solutions are intrinsically incompatible with the IP multimedia subsystem (IMS), the service provisioning framework adopted by the major telecommunication players. We look at ways to develop P2P applications over IMS, identifying the essential service components that pave the way toward interoperable P2P. We discuss the added value that a P2P-IMS solution offers to all parties involved in the service provisioning chain: content provider, third-party service provider, network operator, and ultimately, the user. P2P-IMS brings the power of P2P (increased scalability, availability, resilience, and resource utilization) to the future domain of services, creating a wealth of new business opportunities. Our findings are supported by an IMS-compliant prototype, including a variety of applications.